Triaxial Creep Test and Particle Flow Simulation of Coarse-Grained Soil Embankment Filler - He, Zhongming; Xiang, Da; Liu, Yaxin (Frontiers in Earth Science, 2020)
In order to study the creep characteristics of the coarse-grained soil as embankment filler under long-term vehicle loading, the creep test was performed on coarse-grained soil using the large scale dynamic and static triaxial instruments, and the creep process of the coarse-grained soil sample was simulated by PFC3D software, and the internal particle motion and energy change during the deformation process were studied. The research results show that the coarse-grained soil embankment filler has nonlinear creep characteristics. At a low stress level, the coarse-grained soil is in the stage of elastic deformation. At a high stress level, the final creep deformation curve of the coarse-grained soil does not converge; The creep process is a process in which the particles are distorted and rotated, changing from an unstable state to a stable state. During this process, the particle energy is dissipated to the minimum, and the creep of the sample reaches a stable state; This understanding of particle motion and energy changes during the triaxial creep test of coarse-grained soil will help deepen the understanding of creep characteristics of coarse-grained soil and provide a reference for engineering practice.